Tact instruction for children with autism spectrum disorder: A review. (February 2021) - Bak, MY Savana; Dueñas, Ana D; Avendaño, Sarah M; Graham, Ariel C; Stanley, Tavon
Tacts facilitate social interaction, and a strong tact repertoire can lead to the development of other verbal operants. For children with autism spectrum disorder (ASD), the development of a tact repertoire can reduce stereotypical and repetitive language and increase social communication, as functional language may reduce the amount of stereotypical vocal behavior that children engage in. However, teaching tact repertoires to children with ASD that maintain and generalize is difficult. The current study reviewed tact interventions for children with ASD from 2000 to 2019 to provide an overview of current tact interventions, their effectiveness, and the inclusion of intervention components that may promote maintenance and generalization of learned tacts in children with ASD. Fifty-one studies were included in the review. Of the studies that met criteria for effect size calculations 87.18% of the interventions showed excellent or high effect. Although many of the studies focused more on stimulus control to answer specific research questions, some studies implemented intervention components and procedures that could promote acquisition and generalization of learned tacts in children with ASD. We discuss implications and the need to increase research regarding tact intervention components that can increase generalization in children with ASD.